Gambaran Sumber Stress Dan Strategi Coping Masyarakat Kabupaten Tana Tidung Saat Masa Pandemi Covid-19 - Cici Ismuniar Undunsyah; Sri Sunarni (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2021)
At the beginning of 2020, the world was shocked by the outbreak of the corona virus (Covid-19) which has infected almost all countries in the world. The Ministry of Health has designated local Transmission areas in North Kalimantan, namely Bulungan Regency and Malinau Regency. The impact of COVID-19 on Individuals and Communities can increase stress and anxiety, both because of fear of catching the virus and also because of uncertainty about how the outbreak will affect us socially and economically. The purpose of this study was to describe the level of stress and stress coping of the people of Tana Tidung Regency during the Covid-19 period. This research method uses a quantitative approach that is descriptive in nature, this study has respondents from among workers and non-workers, ages from 19-55 years. The results of the research show that the people of Tana Tidung Regency have a low stress level. This occurs because the first few factors the community has understood the appropriate strategy if they experience a problem, the strategy that is often used by the people of Tana Tidung Regency in dealing with stress is Emotion Focused Coping (EFC), besides that the second factor - on average, the subject is another working community, Tana Tidung Regency Government has handled it very well during the Covid-19 period.